Host specificity, infrequent major host switching and the diversification of highly host‐specific symbionts: The case of vane‐dwelling feather mites. Issue 2 (26th November 2017) - Doña, Jorge; Proctor, Heather; Mironov, Sergey; Serrano, David; Jovani, Roger
Abstract: Aim: Highly host‐specific symbionts are very rarely found except with their typical host species. Although switches to new hosts are rare and difficult to detect, a switch to a host phylogenetically distant from the original one (a 'major host switch') could allow diversification of the symbionts onto the new host lineage. The consequences of such major host switches on the diversification of highly host‐specific symbionts of animals have rarely been explored. Here, we examine the host specificity of vane‐dwelling feather mites, a group that shows strong specificity, together with their host‐switching dynamics and the consequences of major host switches for their diversification. Location: Global. Time period: From 1882 to 2015. Major taxa studied: Feather mites and birds. Methods: Using the largest published dataset of feather mite–bird associations, we analysed raw, phylogenetic and geographical host specificity of feather mites. We studied host‐switching dynamics by describing the sharing by feather mites of bird species with different phylogenetic distances. For three of the most species‐rich feather mite families, we quantified the consequences of major host switches for feather mite diversification. Results: Most feather mite species (84%) inhabit one to three very closely related host species. Assemblages of feather mites on birds do not show a geographical signature, but rather show strong host‐driven structuring. The probability that a mite species occurs on two host species decays sharply with host phylogenetic distance, with only one instance of a feather mite species occupying distantly related hosts from different orders. However, results suggest that despite the strong host specificity, a few major host switches triggered the origin of 21% of the species and 38% of the genera of the mite families studied. Main conclusions: We show that feather mites are highly host‐specific symbionts, whose assemblages do not show geographical structure, even at a continental scale. We conclude that major host switches are very rare events with strong macroevolutionary consequences for feather mite diversity.